Maternal, newborn and breast milk concentrations of elexacaftor/tezacaftor/ivacaftor in a F508del heterozygous woman with cystic fibrosis following successful pregnancy - Ripani, Pietro; Mucci, Matteo; Pantano, Stefano; Di Sabatino, Maria; Collini, Francesca; Ferri, Giulia; Romano, Mario; Recchiuti, Antonio (Frontiers in Medicine, 2023)
With the advent of elexacaftor/tezacaftor/ivacaftor (ETI) more women with cystic fibrosis (CF) are likely to grow families. Hence, understanding long-term safety and effects of CFTR modulators on fertile women and children while monitoring their concentrations is crucial. Here, we report the development of improved LC-MS/MS methodology to measure ETI concentrations in maternal and child blood and breastmilk, applied in one case of successful pregnancy of a 30 years-old woman with CF (F508del/R334W). We observed that ETI remains stable in breastmilk, is absorbed by the infant and can be detected in child plasma. Our results confirm accumulating evidence of successful pregnancy in women treated with CFTR modulators without significant side effects on the child and provide valuable analytical procedures suitable for the post-marketing evaluation of CFTR modulators in pregnant and lactating women, as well as in their infants.